Biomarker as a research tool in linking exposure to air particles and respiratory health - Suhaimi, Nur Faseeha; Jalaludin, Juliana (Hindawi Publishing Corporation, 2015)
Some of the environmental toxicants from air pollution include particulate matter (PM10), fine particulate matter (PM2.5), and ultrafine particles (UFP). Both short- and long-term exposure could result in various degrees of respiratory health outcomes among exposed persons, which rely on the individuals’ health status. Methods. In this paper, we highlight a review of the studies that have used biomarkers to understand the association between air particles exposure and the development of respiratory problems resulting from the damage in the respiratory system. Data from previous epidemiological studies relevant to the application of biomarkers in respiratory system damage reported from exposure to air particles are also summarized. Results. Based on these analyses, the findings agree with the hypothesis that biomarkers are relevant in linking harmful air particles concentrations to increased respiratory health effects. Biomarkers are used in epidemiological studies to provide an understanding of the mechanisms that follow airborne particles exposure in the airway. However, application of biomarkers in epidemiological studies of health effects caused by air particles in both environmental and occupational health is inchoate. Conclusion. Biomarkers unravel the complexity of the connection between exposure to air particles and respiratory health.